Perfil epidemiológico da raiva na região Noroeste do Estado de São Paulo no período de 1993 a 2007 - Queiroz, Luzia Helena [UNESP]; Carvalho, Cristiano De [UNESP]; Buso, Daniel Sartori [UNESP]; Ferrari, Clara Isabel De Lucca; Pedro, Wagner André [UNESP] (Sociedade Brasileira de Medicina Tropical - SBMT, 2009)
The epidemiology of animal rabies in the region of Araçatuba, in the northwest of São Paulo State, from 1993 to 2007, is described according to the results from diagnoses made at laboratories in the region, using the fluorescent antibody and mouse inoculation tests. Out of 10,579 samples analyzed, 4.9% were positive (518/10,579). Dogs accounted for 67% of the cases (346/518) and these occurred between 1993 and 1997. Among the other positive samples, 16% (84/518) were in cattle and 9.7% (50/518) were in bats. Among the 42 municipalities in the region, 23 (55%) presented at least one rabies-positive case, while 13 of them had cases in bats. Three distinct cycles of rabies were identified in the northwestern region of the State of São Paulo: the urban cycle characterized predominantly by canine rabies (1993 to 1997); and the aerial and rural cycles starting in 1998, with predominance of cases in bats in urban areas and in herbivores.

Descreve-se a epidemiologia da raiva animal na região de Araçatuba, noroeste do estado de São Paulo, durante o período de 1993 a 2007, com base nos resultados dos diagnósticos realizados em laboratórios da região, utilizando as técnicas de imunofluorescência direta e inoculação intracerebral em camundongos. De 10.579 amostras analisadas, 4,9% foram positivas (518/10.579). Os casos em cães corresponderam a 67% (346/518) do total e ocorreram entre 1993 a 1997. Dentre as demais amostras positivas, 16% do total (84/518) foi detectado em bovinos e 9,7% (50/518) em morcegos. Dos 42 municípios da região, 23 (55%) apresentaram pelo menos um caso positivo da doença, sendo que 13 deles registraram casos em morcegos. Foram identificados três ciclos distintos da raiva na região Noroeste do Estado de São Paulo, o ciclo urbano caracterizado predominantemente pela raiva canina (1993 a 1997) e os ciclos aéreo e rural, a partir de 1998 com predominância de casos em quirópteros nas áreas urbanas e em herbívoros.
Epidemiological profile of rabies in the northwestern region of São Paulo State, from 1993 to 2007
Keywords: Rabies; Epidemiology; Laboratory diagnosis; Bats; Chiroptera; Raiva; Epidemiologia; Diagnóstico laboratorial; Morcegos; Chiroptera